2014
DOI: 10.1155/2014/373295
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis and Protection Mechanisms Action of Medicinal Plants Targeting Apoptosis of Hepatocytes and Hepatic Stellate Cells

Abstract: Following chronic liver injury, hepatocytes undergo apoptosis leading to activation of hepatic stellate cells (HSC). Consequently, activated HSC proliferate and produce excessive extracellular matrix, responsible for the scar formation. The pandemic trend of obesity, combined with the high incidence of alcohol intake and viral hepatitis infections, highlights the urgent need to find accessible antifibrotic therapies. Treatment strategies should take into account the versatility of its pathogenesis and act on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 90 publications
0
31
0
1
Order By: Relevance
“…Therefore, modulating above‐mentioned pathways in injured hepatocytes is one of critical therapeutic strategies to treat acute or chronic liver injury. Currently, there is no successful or standard treatment for acute or chronic liver injury concerning apoptosis, although numerous studies have shown that pharmaceutical drugs and medicinal plants can inhibit apoptosis in pathologic condition of liver (Duval, Moreno‐Cuevas, Gonzalez‐Garza, Rodriguez‐Montalvo, & Cruz‐Vega, ). Although pharmaceutical drugs are one of the widely used options for treating several diseases including cancer, these drugs have critical side effects as well as high cost of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, modulating above‐mentioned pathways in injured hepatocytes is one of critical therapeutic strategies to treat acute or chronic liver injury. Currently, there is no successful or standard treatment for acute or chronic liver injury concerning apoptosis, although numerous studies have shown that pharmaceutical drugs and medicinal plants can inhibit apoptosis in pathologic condition of liver (Duval, Moreno‐Cuevas, Gonzalez‐Garza, Rodriguez‐Montalvo, & Cruz‐Vega, ). Although pharmaceutical drugs are one of the widely used options for treating several diseases including cancer, these drugs have critical side effects as well as high cost of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory cellular infiltration observed in Group III “KBrO 3 rats” in this study was associated with the presence of huge amount of collagen fibers around the portal zone and extended between cords of hepatocytes. This may be due to the damage and dysfunction of mitochondria caused by the reactive oxygen species with lipid peroxidation products leading to cell apoptosis and necrosis and stimulation of a cascade leading to fibrosis and collagen deposition (Duval et al, ). The deposition of collagen fibers in KBrO 3 rats’ livers was concomitant with the significant increase in the immunoexpression of HSC markers “GFAP.” HSCs play an important role in liver fibrosis due to the deposition of collagen type I and III and matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the process of hepatic stellate cells (HSCs) turning from quiescent state to activation state plays a central role in the development of hepatic fibrosis . Activated HSCs activate into myofibroblasts, resulting in deposition and unbalanced degradation of extracellular matrix (ECM) . Previous studies have shown that soluble egg antigens (SEA) from Schistosoma japonicum ( S. japonicum ) and Schistosoma mansoni ( S. mansoni ) can inhibit HSC proliferation and activation .…”
Section: Introductionmentioning
confidence: 99%